Increasing the Readiness of Vocational School Teachers for Competition in the Industry 4.0 Era by Strengthening Practical and Transferable Skills - Ahmad Rifqi Hidayat; Ninik Sri Rahayu; Nur Ellyanawati Esty Rahayu (Jurnal Pengabdian Masyarakat Bestari, 2023)
This research aims to improve the competency and expertise of Vocational School (VS) teachers majoring in Sharia Banking by strengthening their practical and soft skills. This program has two primary outcomes: first, an increase in vocational teachers' knowledge and practical skills, and second, sending four participants to obtain professional competency certification at basic career levels. Such programs for educators need to be further developed in the future so that VSs can generate graduates who are ready to compete in the Industry 4.0 era.